Damage evaluation of surrounding rocks subjected to dynamic internal unloading and external loading - Ming Tao; Gongliang Xiang; Rui Zhao; Jinjie Liu (Tunnelling and Underground Space Technology, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Dominant taxa, rather than Shannon diversity, drive zooplankton stability across scales - Zeng Lei; Zhang Rui; Chen Yuxiang; Liu Beibei; Zheng Tingting; Li Wuhui; Tang Yuqi; Li Yating; Xiang Yuqi; Nie Mengwei; Chen Guobao (Estuarine, Coastal and Shelf Science, 2026)

NO-responsive microgel encapsulated Ce-MOF nanozymes loaded with gastrodin for synergistic rheumatoid arthritis therapy - Xiang Zou; Yicheng Liu; Pingli Dong; Haoyu Qiu; Rui Wen; Lanling Dai; Linzhu Yu; Fang Lan; Yao Wu (Chemical Engineering Journal, 2026)

A hybrid machine learning and data assimilation framework for penman–monteith evapotranspiration estimation over China - Xiaowen Wu; Xiang Li; Jianli Ding; Shaomin Liu; Tongren Xu; Lisheng Song; Sayed M. Bateni; Ziwei Xu; Dongxing Wu; Xinlei He; Jinjie Wang; Rui Liu; et al. (Remote Sensing of Environment, 2026)

Bearing capacity envelopes of wide-shallow bucket foundations in sand under combined horizontal and moment loading - Run Liu; Rui Zhou; Xiang-chuan Meng; Yu Wang (Ocean Engineering, 2026)

Interface-observation-based reconstruction of rising-bubble flow fields using phase-field finite-volume physics-informed neural networks - Zhiyuan Geng; Rui Deng; Xiang Yu; Hailong Liu; Hang Ren; Shengze Cai (Ocean Engineering, 2026)

Microwave coupled ultrasound pretreatment for enhancing acid leaching of ilmenite and its mechanism - Rui Liu; Long Xiang; Tao Long; Wenrong Xiang; Jiahao Hu; Li Li; Chunhui Han; Xingran Zhang (Minerals Engineering, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Experimental investigation of the gas desorption–diffusion behavior of multi-scale outburst-prone coal under constant desorption pressures - Chaojun Fan; Rui Zhu; Lei Yang; Mingkun Luo; Xiang Fu; Xuan Liu; Xiaofeng Jiang (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

WaveUNet: An efficient deep network based on discrete wavelet transform and attention mechanism for InSAR phase unwrapping - Wenfei Mao; Hongquan Xiang; Xue Cheng; Guoxiang Liu; Xiaowen Wang; Rui Zhang; Oriol Monserrat; Michele Crosetto (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Revealing the flavor deterioration and key off-odor compounds in garlic paste during processing and storage: A complementary approach with GC-MS, GC-IMS, and GC-O-MS - Weihe Zhu; Lu Xiang; Yunge Liu; Shanshan Zhou; Rui Lin; Zhenjia Zheng; Rentang Zhang; Bin Zhang (Food Chemistry, 2026)

The gut microbial metabolism of structurally varied procyanidin oligomers: Focus on metabolites and their characteristics - Chunyi Liu; Ruonan Liu; Qun Lu; Mo Zhang; Xiang Liu; Xiue Jin; Rui Liu (Food Bioscience, 2026)

Characterization and classification of a novel bacteriophage, vB_RsoP_HXg1W, infecting Ralstonia pseudosolanacearum: a new member of the genus Serkorvirus in the family Autotranscriptaviridae - XiaoLi Yu; Zheng Fang; Qingshan Wu; Rui Wu; Chuangen Lin; Lan Xiang; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Distributed nonlinear placement problems in the NASVs with nonsmooth objectives and unknown time-varying actuator faults - Wen-Jin Liu; Rui-Qi Cao; Xinxin Zhang; Xiang-Yu Yao; Ming-Feng Ge (Ocean Engineering, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Bioaerosol multi-pollutant source localization in urban microclimates using an improved particle swarm optimization method with restricted search capabilities - Zhijian Liu; Yixiang Ma; Chenxing Hu; Haiyang Liu; Hongliang Zhang; Xin Li; Zhenhai Sun; Rui Rong; Zhijian Dong; Xiang Zhao; Guangpeng Yao (Sustainable Cities and Society, 2026)

The fate of exogenous organic matter on ferrihydrite: Critical controls of saturation on carbon and nitrogen sequestration - Fei Chen; Yichen Wu; Leyun Wang; Mengting Zhu; Rui Liu; Xiang Liu; Guanghe Li; Miao Li (Journal of Environmental Management, 2026)

MicroRNA-132 Alleviates Ischemia-Reperfusion-Induced Neuronal Apoptosis by Targeting Mecp2 in Stroke Models - Xiang Wang; Rui Ma; Zilu Liu; Wenjin Sun; Lin Xia; Yurou Wang; Donghua Shao; Caixia Sun (Neurotoxicity Research, 2026)

Position dependent elasticity of the anterior talofibular ligament in healthy young women: an in-vivo shear wave elastography study - Zili Chen; Wan Zhou; Hao Liang; Xing Liu; Yibo Li; Li Yang; Huijuan Xiang; Rui Du (European Journal of Applied Physiology, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

A preliminary assessment of ocean wave parameter retrieval and wave energy estimation using spaceborne BDS-R data - Jinwei Bu; Shuhui Liu; Shunshuang Xu; Hui Yang; Tongsu Xiang; Xin He; Yuhang Jiang; Rui Li (Ocean Engineering, 2026)

Study on the effects of gestational arsenic exposure on the developmental toxicity of brain tissue in mice offspring using network toxicology and RNA-seq - Zitong Wang; Wenjin Qiao; Ruigang Liu; Yuan Lv; Binjie Niu; Tianxu Li; Mengling Zhang; Yanhui Xiang; Rui Qiao; Dapeng Tai (Food and Chemical Toxicology, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Fabrication of phosphorus@carbon nanotube/Ti4O7 composite anode for enhanced electrochemical degradation of norfloxacin: Nonmetal doping strategies and associated mechanisms - Pingzhou Duan; Haiyang Wang; Rui Pang; Chuanyu Zhang; Lixia Zheng; Yifei Zhang; Li Liu; Xiang Hu; Jian Wei (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Six-component load reconstruction for offshore wind turbine blades considering deformation-induced additional moments - Baoxuan Wang; Xu Liang; Lizhong Wang; Fangyuan Sheng; Xiang Wang; Yue Chen; Jianwei Zhang; Shengjie Rui; Rui Liu (Ocean Engineering, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Dual-phase Co/CoFe nanoparticles anchored on N, F co-doped hollow carbon microcapsules as efficient bifunctional catalysts for aqueous/quasi-solid-state Zn-air batteries - Bin Cui; Yunfeng Zhu; Xingyue Fang; Renjing Du; Jiabao Bai; Mengran Li; Wanting Xiang; Wenxuan Xie; Yana Liu; Jiguang Zhang; Rui Shi; Jun Wang; et al. (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Coupling data assimilation and machine learning to improve land surface conditions and near-surface temperature and humidity forecasts - Xinlei He; Shaomin Liu; Tongren Xu; Fei Chen; Zhitao Wu; Ziwei Xu; Xiang Li; Rui Liu (Agricultural and Forest Meteorology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Leaching mechanism and kinetics investigation of ilmenite leaching assisted by iron powder - Tao Long; Long Xiang; Rui Liu; Congxue Tian; Li Li; Jiesong Liu; Wenrong Xiang (Minerals Engineering, 2026)

Effect of enzyme-induced carbonate precipitation on nitrogen loss from sheet erosion on purple soil slopes in the Three Gorges Reservoir area - Hai Xiao; Jiejie Hou; Lun Zhang; Rui Xiang; Deyu Liu; Feng Gao; Yu Ding; Zhenyao Xia (Journal of Water Process Engineering, 2026)

Precambrian crustal evolution of the southern margin of the North China Craton: Evidence from the Paleo–Mesoproterozoic sedimentary rock - Shuo Wang; De-Bin Yang; Xiang-Yu Yan; Ke Wu; Jian-Ning Liu; Rui-Qing Xue (Journal of Asian Earth Sciences, 2026)

Interfacial environment modulation by nanoneedle-shaped polyaniline for enhanced hydrogen isotope separation by water electrolysis - Rui Li; Guoyu Li; Penghui Xiong; Yuhan Wu; Ruidong Liu; Hang Zhong; Yue Yao; Xin Xiang; Wenhua Luo; Jingsong Xu (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

An enhanced GNSS/INS positioning method with position and attitude constraints in urban environments - Jianhui Cui; Xuan Han; Rufei Liu; Rui Tu; Yan Xiang; Shuangshuang Wu; Zeyu Li; Wenqian Zhou (GPS Solutions, 2026)

Mitochondria to nucleus/nucleolus migration probe for in-situ and dual-color visualization of MMP alteration and monitoring apoptosis - Mengmeng Wei; Derong Xiang; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Jing Xu; Xiaoyan Tang; Qijian Zhang; Zhida Han; Xifeng Yang; Rui Yang (Analytica Chimica Acta, 2026)

Genome-wide identification of TGA transcription factors in wheat and the TaTGA13 negatively modulates stripe rust resistance - Jiajie Liu; Rui Li; Mingjie Xiang; Xunyin Yuan; Yifan Tian; Xuanqi Zhang; Jingyao Wang; Jianhui Wu; Qingdong Zeng; Dejun Han (Plant Science, 2026)

Cumulative leaching behavior in sustainable vanadium extraction from V-slag using Ba-Slag - Hong-Rui Yue; Ya-Kun Zhao; He Yang; Xiang-Xin Xue; Jing Liu (Minerals Engineering, 2026)

Enhanced evapotranspiration prediction by incorporating plant stomatal-hydraulic co-regulation into hydrological model - Yong Liu; Tiesong Hu; Huandi Li; Xiang Zeng; Rui Zhu; Peiran Jing; Qifan Zhang; Xiang Li; Yanxuan Wang (Journal of Hydrology, 2026)

Topology optimization of porous electrodes for enhanced mass transport and electrochemical performance - Qiqi Zhang; Bing Yi; Rui Liu; Xiang Peng (Chemical Engineering Journal, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Reconstruction of high-precision gridded precipitation dataset in the alpine cold regions of the Qilian Mountains: An intelligent technological framework from downscaling to calibration - Renjun Wang; Xiang Qin; Yushuo Liu; Jianyu Zhao; Rui Zhang; Zizhen Jin; Yanzhao Li; Wentao Du; Jizu Chen; Weijun Sun (Atmospheric Research, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

The association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with surrogate indicators of insulin resistance: a panel study - Sha You; Lin Liu; Min Xiang; Lei Zhao; Wenting Guo; Xiaomin Zhang; Rui Zhu; Liangle Yang (Environmental Geochemistry and Health, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

From plant-based food waste to biochar: A green strategy for agri-food supply chain waste valorization–a comprehensive review - Xuejiao Chen; Yanbo Hao; Wei Lin; Liya Xie; Rui Yang; Wenliang Xiang; Zhilian Gong; Feng Gu; Hongyan Liu; Jie Tang (Trends in Food Science & Technology, 2025)

Mitigation performance and mechanism of the EICP for the erosion resistance of purple soil to concentrated flow in the Three Gorges Reservoir area - Deyu Liu; Ruidong Yang; Lun Zhang; Zhenyao Xia; Zhiyong Zhang; Rui Xiang; Feng Gao; Wenqi Zhang; Yu Ding; Hongqiang Shi; Hai Xiao (Soil and Tillage Research, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Bioinspired mortise-tenon interlocking HKUST-1/CuOH micro-nano architectures on stainless steel mesh for oil-water separation membranes - Xiang Li; Ping Zhang; Rui Wang; Meng Zhu; Xiaobo Gong; Yucheng Liu (Environmental Research, 2025)

Electronic tuning of MoS2 nanosheets by Ag atoms doping for efficient hydrogen evolution reaction - Xiang Liu; Hongjie Zhu; Rui Lu; Hongsen Wei; Huijie Sun; Yumo Wang; Ailing Zhang; Kexin Lv; Lei Zhang; Haibin Zhang; Hengcheng Wan (Process Safety and Environmental Protection, 2025)

Fusarium infection alters the effects of vegetable residue and its compost on nitrous oxide emissions from acid soil - Yumeng Xu; Xiaoxiao Xiang; Waqar Ahmed; Junhui Yin; Owen Fenton; Wenxuan Shi; Jiaqi Wang; Ruixue Chang; Rui Liu; Hao Chen; Guorong Xin; Qing Chen (Applied Soil Ecology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Enhancing the participation of water in the anaerobic digestion of sewage sludge for highly efficient methanogenesis - Jiachang Cao; Ying Xu; Chen Zhang; Xiang Li; Rui Liu; Xueye Wang; Xiaohu Dai (Water Research, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Uncovering the transcriptional regulatory network underlying selenium tolerance in maize seedlings - Rui Wang; Hualei Zhang; Zihan Liu; Yingao Lu; Shouxin Lan; Bin Zhang; Shuai Li; Qian Li; Jingyu Ma; Xiaoli Xiang; Changsheng Li (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Submersion deteriorates the mechanical properties of Cynodon dactylon root and alters its failure type - Deyu Liu; Zhubao Chen; Lun Zhang; Zhenyao Xia; Rui Xiang; Feng Gao; Qianheng Zhang; Ruidong Yang; Yu Ding; Yueshu Yang; Hai Xiao (Plant and Soil, 2025)

Estimation of Soil Organic Carbon Stocks Utilizing Machine Learning Algorithms and Multi-source Geospatial Data in Coastal Wetlands of Tianjin and Hebei, China - Rui Yang; Mingyue Liu; Yongbin Zhang; Weidong Man; Jingfen Tong; Dong Liu; Qingwen Zhang; Caiyao Kou; Xiang Li; Yahui Liu; Di Tian; Xuan Yin; et al. (Chinese Geographical Science, 2025)

Propagation threshold from meteorological to agricultural drought and its potential influence factors - Peng Sun; Ruilin Liu; Rui Yao; Xihui Gu; Aminjon Gulakhmadov; Dongdong Kong; Xiang Zhang (Journal of Hydrology, 2025)

Substrate type-driven differences in interfacial microbial community and pathogenic risk: Clay, microplastics and activated carbon - Taishuo Zhang; Wenfu Wang; Xiang Zhi; Xiaoqian Ye; Rui Wang; Jiarui Zhao; Jiamin Dai; Hong Qiang; Peng Liu; Hanzhong Jia (Gondwana Research, 2025)

Soil myxomycete community in temperate cropland and influence of straw turnover - Feng-Yun Zhao; Guan-Xiu Guan; Rui-Xuan Xiang; Bai-You Chen; Jing Feng; Jian Liu (Applied Soil Ecology, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Study on the flame retarding mechanism of HFC-134a on hydrocarbon refrigerants - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Xiangnong Liu; Qingqing Li; Lei Tang; Ke Wang (International Journal of Refrigeration, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

White matter microstructural and cognitive function changes in bipolar depression patients with suicidal ideation - Junfan Liang; Rui Fan; Xinyin Guo; Hua Liu; Xuehua Li; Jixiang Yuan; Kezhi Liu; Xuemei Liang; Bo Xiang (Brain Imaging and Behavior, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Vanadium recovery with barium slag as a roasting additive: A novel waste-to-value approach - Hong-Rui Yue; Ya-Kun Zhao; Xiang-Xin Xue; Jing Liu (Journal of Cleaner Production, 2025)

Low-damage performance of rocking column bases with Belleville Springs for enhanced seismic resilience - Jiang-Yue Xie; Zhenduo Yan; Junrong Liu; Rui Zhang; Ping Xiang; Xianzhong Zhao; Gregory A. MacRae; G. Charles Clifton; Rajesh P. Dhakal; Shahab Ramhormozian; Geoffrey Rodgers; Pierre Quenneville; et al. (Engineering Structures, 2025)

L-arginine-enhanced PEI-based polyamide Nanofiltration membranes for efficient heavy metal ion removal - Junwei Li; Shan Wang; Qingjuan Zhu; Daliang Xu; Yongmei Wang; Xi Zhang; Jiale Du; Qin Chen; Rui Zhao; Xiang Hu; Yong Liu; Raf Dewil; et al. (Desalination, 2025)

Superior matching between electrochemical and non-electrochemical reactions to boost furfural electro-oxidation - Jianyuan Deng; Rui Li; Kun Xiang; Longzhou Zhang; Kaihang Sun; Young Dok Kim; Zhongyi Liu; Jingmin Ge; Zhikun Peng (Chemical Engineering Journal, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Global analysis and prediction of the occurrence and fate of PFASs in dumpsites - Rui Xiang; Guangyuan Yao; Can Qian; Yuqiang Liu; Ya Xu; Qifei Huang (Resources, Conservation and Recycling, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Streptomyces adonidis sp. nov., a novel actinomycete strain with antifungal activity isolated from the root of Adonis amurensis Regel - Rui Du; Hui Bing; Wentian Lu; Congting Gao; Fanxue Kong; Hongtu Wang; Yue Shen; Chongxi Liu; Wensheng Xiang (Antonie van Leeuwenhoek, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Analysis of the city-scale wind environment and detection of ventilation corridors in high-density metropolitan areas based on CFD method - Rui Liu; Yuxiang Wang; Yu Zhang; Zhixing Peng; Hankai Chen; Xiang Li; Hang Li; Weiyue Li (Urban Climate, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Microplastic effects on soil nitrogen cycling enzymes: A global meta-analysis of environmental and edaphic factors - Yangzhou Xiang; Bin Yao; Josep Peñuelas; Jordi Sardans; Luca Nizzetto; Rui Li; Ying Liu; Yang Luo; Mari Räty; Jian Long; Yuan Li (Journal of Hazardous Materials, 2025)

Regulation of multilayer long crystalline MoS2 by NiO-modified Al2O3 for improved hydrodesulfurization of COS - Yubiao Li; Yu Liu; Xueqian Wang; Yixing Ma; Ping Ning; Langlang Wang; Xiang Li; Rui Cao (Environmental Research, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Spatial and temporal evolution and factors influencing soil aggregate stability in the riparian zone during exposure: A case study of the water-level fluctuation zone of the Three Gorges Reservoir, China - Yuanzhen Ni; Zhenyao Xia; Yueshu Yang; Deyu Liu; Rui Xiang; Yu Ding; Huan Hong; Di Wang; Hai Xiao (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Curcumin protects porcine granulosa cells and mouse ovary against reproductive toxicity of aflatoxin B1 via PI3K/AKT signaling pathway - Sihong Li; Rui Li; Jun Jiang; Lu Liu; Xiang Ma; Tao Wang; Lili Zhao; Weifen Li; Dong Niu (Environmental Pollution, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Zirconium based metal–organic frameworks with aggregation-induced electrochemiluminescence for sensitive analysis of aflatoxin B1 by signal dual-amplification strategy - Yuan Li; Xue Dong; Tingting Wu; Xiaoyue Zhang; Xiang Ren; Rui Feng; Yu Du; Jin Yong Lee; Xuejing Liu; Qin Wei (Chemical Engineering Journal, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Hybrid packed bed bioreactor using combined biodegradation and ozonation to enhance nitrogen and micropollutants removal from landfill leachate - Xuetong Yang; Ze Liu; Changtao Chen; Tao Zhang; Qintong Wang; Rui Zhang; Feng Duan; Xiang Tian; Mingshui Yao; Kristof Demeestere; Stijn W.H. Van Hulle (Bioresource Technology, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Environmental safety performance dynamics and estimation of the deterioration of leachate containment elements: Implications for the lifespan of hazardous waste landfills - Rui Xiang; Can Qian; Guangyuan Yao; Yuqiang Liu; Heyu Du; Ya Xu; Qifei Huang (Journal of Cleaner Production, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Magnetic porous microspheres altering interfacial thermodynamics of sewage sludge to drive metabolic cooperation for efficient methanogenesis - Hui Geng; Ying Xu; Rui Liu; Jun Xu; Xiang Li; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Proteins in hydrothermal carbonization liquor of sewage sludge interfere with vivianite crystallization for phosphorus recovery - Yue Zhang; Xiaofan Yang; Xinran Zhang; Dezhi Sun; Xinyi Liu; Rui Lan; Min Zheng; Mark C.M. van Loosdrecht; Xiang Cheng (Resources, Conservation and Recycling, 2024)

Release dynamics, risk evolution and driving mechanisms of heavy metals in superalkaline fly ash co-disposed by MSW landfill - Zhaozhi Jia; Ya Xu; Rongbin Xu; Rui Xiang; Shuna Sun; Changxin Nai; Yuqiang Liu (Environmental Pollution, 2024)

A Janus textile mimics leaf stoma for dynamic thermal regulation through a shape memory coating - Yuanxiang Xiao; Rui Cai; Shuangfei Xiang; Shujun Zhao; Feiya Fu; Hongyan Diao; Xiangdong Liu (Chemical Engineering Journal, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Full title: The performance evaluation of marine ecological civilization construction (MECC): A case study of coastal cities in Jiangsu Province, China - Yang Yang; Dingwu Liu; Rui Xu; Zhuona Li; Chenwei Shi; Xiaodong Zhu; Xiang Sun (Ocean & Coastal Management, 2024)

Zircon U–Pb geochronology and geochemistry of Paleoproterozoic quartz monzonite in the Northern Yangtze Craton: Petrogenesis and geological implications - Wen-Xiang Zhang; Rui Li; Guang-Yan Zhou; Zhi-Fu Liu; Yuan-Bao Wu (Precambrian Research, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Manganese oxides/graphene aerogels as lightweight microwave absorbers for extreme environment application - Jieping Wang; Shaohua Shi; Yongzhu Yan; Gengping Wan; Haoxiang Zhai; Xiang Yuan; Liang Li; Changlong Du; Rui Liu; Guizhen Wang (Chemical Engineering Journal, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Release potential, neglected leakage and reduction countermeasures of COD and Ammonia in MSWLs - Haonan Yang; Qifei Huang; Ya Xu; Rui Xiang; Yuqiang Liu (Science of The Total Environment, 2024)

Cytotoxic withanolides from the stems and leaves of Physalis ixocarpa - Ke Xiang; Yan Liu; Rui Zhu; Yang Xu; Dejuan Sun; Yueying Yang; Yushu Yan; Bingyou Yang; Hua Li; Lixia Chen (Food Chemistry, 2024)

Evaluating the influence of Cynodon dactylon on the wave force and wave erosion in the water-level fluctuation zone of the Three Gorges Reservoir Area - Hai Xiao; Deyu Liu; Feng Gao; Rui Xiang; Wenqi Zhang; Zirui Liu; Chaohuan Ye; Lun Zhang; Zhenyao Xia (Ecological Engineering, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Two microbes assisting Miscanthus floridulus in remediating multi-metal(loid)s-contaminated soil - Yunhua Xiao; Jingjing Ma; Rui Chen; Sha Xiang; Bo Yang; Liang Chen; Jun Fang; Shuming Liu (Environmental Science and Pollution Research, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Characterization of CYP82 genes involved in the biosynthesis of structurally diverse benzylisoquinoline alkaloids in Corydalis yanhusuo - Xiuyu Liu; Ying Ma; Junling Bu; Conglong Lian; Rui Ma; Qishuang Li; Xiang Jiao; Zhimin Hu; Yun Chen; Suiqing Chen; Juan Guo; Luqi Huang (Plant Molecular Biology, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Factors affecting chemical and textural properties of dried tuber, fruit and vegetable - Yue Li; Han Zhao; Kexin Xiang; Dajing Li; Chunju Liu; Haiou Wang; Wenqian Pang; Liying Niu; Rui Yu; Xiyun Sun (Journal of Food Engineering, 2024)

Failure mechanism of rock masses with complex geological conditions in a large underground cavern: A case study - Jin-Shuai Zhao; Shu-Qian Duan; Bing-Rui Chen; Lei Li; Ben-Guo He; Peng-Xiang Li; Guo-Feng Liu (Soil Dynamics and Earthquake Engineering, 2024)

Seismic performance of LNG tanks in deep soil site considering soil-foundation-structure interaction - Zaixian Li; Su Chen; Rui Zhang; Xiang Liu; Xiaojun Li (Soil Dynamics and Earthquake Engineering, 2024)

Tourism development potential and obstacle factors of cultural heritage: Evidence from traditional music in Xiangxi - Xianyong Zhang; Baofa Peng; Lulu Zhou; Chunyang Lu; Yali Wang; Rui Liu; Hui Xiang (Journal of Geographical Sciences, 2024)

Prediction interaction responses between railway subgrade and shield tunnelling using machine learning with sparrow search algorithm - Xiang Liu; Kuichen Li; Annan Jiang; Qian Fang; Rui Zhang (Transportation Geotechnics, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Research progress on the construction of oxygen vacancy defects and application in photocatalytic oxidation of elemental mercury - Xin Yang; Zijian Xiang; Jiang Wu; Ping He; Yongfeng Qi; Shuo Chen; Yizheng Lu; Rui Xie; Zhengyu Liu; Chuman He (Fuel, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Experimental and numerical research on the viscous flow field induced by a swing plate - Rui Deng; Hailong Liu; Xiaoyue Mo; Xiang Yu; Tiecheng Wu; Yulong Li (Ocean Engineering, 2023)

Surface engineered long-lasting antibacterial Janus cotton fabrics with excellent moisture/thermal management properties - Lujie Wang; Maoshuang Chen; Rui Cai; Jingjing Jiang; Shuangfei Xiang; Xiangdong Liu; Hongyan Diao (Chemical Engineering Journal, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Boosting PFOA photocatalytic removal from water using highly adsorptive and sunlight-responsive ZIF67/MIL-100(Fe) modified C3N4 - Peidong Su; Chunhui Zhang; Yu Liu; Junke Zhang; Ridha Djellabi; Rui Wang; Junqiang Guo; Rui Zhang; Hongwei Guo; Xiang Ding; Xinyue Liu (Journal of Environmental Chemical Engineering, 2023)

Development of a novel fluorescent aptasensor based on the interaction between hexagonal β-Co(OH)2 nanoplates and nitrogen-doped carbon dots for ultrasensitive detection of patulin - Qi Sun; Zhijuan Li; Ningxin Liu; Yuting Zhou; Fuyan Zhang; Shuang Li; Peng Jin; Rui Xiang; Tao Le (Analytica Chimica Acta, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Enhanced anode electrochemiluminescence in split aptamer sensor for kanamycin trace monitoring - Xiaoyue Zhang; Yu Du; Xuejing Liu; Rui Feng; Yue Jia; Xiang Ren; Nuo Zhang; Lei Liu; Qin Wei; Huangxian Ju (Food Chemistry, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Effects of EDTA and Organic Acids on Physiological Processes, Gene Expression Levels, and Cadmium Accumulation in Solanum nigrum Under Cadmium Stress - Wanhong Liu; Ting Yu; Hanping Cao; Xiang Peng; Ya Yang; Rui Li (Journal of Soil Science and Plant Nutrition, 2023)

Does physical activity moderate the association between shorter leukocyte telomere length and incident coronary heart disease? Data from 54,180 UK Biobank participants - Meiruo Xiang; Luke C. Pilling; David Melzer; Ben Kirk; Gustavo Duque; Rui Liu; George A. Kuchel; Andrew R. Wood; Brad Metcalf; Breno S. Diniz; Melvyn Hillsdon; Chia-Ling Kuo (GeroScience, 2023)
Telomere shortening is a biological aging hallmark. The effect of short telomere length may be targeted by increased physical activity to reduce the risk of multiple aging-related diseases, including coronary heart disease (CHD). The objective was to assess the moderation effect of accelerometer-based physical activity (aPA) on the association between shorter leukocyte telomere length (LTL) relatively in the population sample and incident CHD. Data were from the UK Biobank participants with well-calibrated accelerometer data for at least 6.5 days ( n = 54,180). Relative mean LTL at baseline (5–6 years prior to aPA assessment) was measured in T/S ratio, using a multiplex quantitative polymerase chain reaction (qPCR) technology, by comparing the amount of the telomere amplification product (T) to that of a single-copy gene (S). aPA measures included total number of events (at least 10-s continued physical activity > 32 milligravities [mg]), total volume, mean duration, mean intensity, and peak intensity of all events. LTL, aPA measures, and their interactions were associated with incident CHD (mean follow-up 6.8 years) using Cox proportional hazards models adjusting for covariates. Longer LTL (relative to the sample distribution) was associated with reduced incidence of CHD (adjusted hazard ratio [aHR] = 0.94 per standard deviation [SD] increase in LTL, [95% CI, 0.90 to 0.99], P = .010). Incidence of CHD was reduced by higher total volume of aPA (aHR = 0.82 per SD increase in LTL, [95% CI, 0.71 to 0.95], P = .010) but increased by higher total number of events (aHR = 1.11 per SD increase in LTL, [95% CI, 1.02 to 1.21], P = .020) after controlling for other aPA measures and covariates. However, none of the interactions between LTL and aPA measures was statistically significant ( P = .171).

Theory, framework, and methodology for physical lifespan prediction of hazardous waste landfills - Xu Ya; Yao Guangyuan; Liu Yuqiang; Liu Jingcai; Xiang Rui; Qian Can (Science of The Total Environment, 2023)

Experimental study on low-frequency flow noise at the stern of a surface vessel induced by pulsating pressure - Rui Deng; Zhenpu Yan; Xiang Yu; Hao Li; Hailong Liu; Tiecheng Wu (Ocean Engineering, 2023)

Experimental study on the influence of a T-foil and bulbous bow on the resistance and motion in regular head waves of trimarans - Rui Deng; Sichong Huang; Shigang Wang; Hailong Liu; Xiang Yu; Tiecheng Wu (Ocean Engineering, 2023)

Antibacterial, antiviral, and biodegradable collagen network mask for effective particulate removal and wireless breath monitoring - Peng Zhao; Rui Wang; Jun Xiang; Jinwei Zhang; Xiaodong Wu; Chaojian Chen; Gongyan Liu (Journal of Hazardous Materials, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Self-shedding of multifunctional biomolecular nanocarriers for H-FABP monitoring in magnetic separation self-powered photoelectrochemical and colorimetric immunoassay platform - Dongquan Leng; Rui Xu; Xiang Ren; Hongmin Ma; Lei Liu; Qin Wei; Huangxian Ju (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Experimental study on low-damage performance of Sliding Hinge Joint - Junrong Liu; Rui Zhang; Zhenduo Yan; Jiang-Yue Xie; Kim Eng Chouery; Liang-Jiu Jia; Ping Xiang; Xianzhong Zhao; Shahab Ramhormozian; Rajesh P. Dhakal; G. Charles Clifton; Gregory A. MacRae (Soil Dynamics and Earthquake Engineering, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

A testis-specific gene doublesex is involved in spermatogenesis and early sex differentiation of the Chinese mitten crab Eriocheir sinensis - Long Wang; Zhi-Qiang Liu; Ke-Yi Ma; Jing-Rui Tao; Xiang Fang; Gao-Feng Qiu (Aquaculture, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Improvement of soybean meal quality by one-step fermentation with mixed-culture based on protease activity - Chuan Wang; Xiaozhi Qiu; Rui Hou; Jun Liu; Li Li; Xiang Mao (Innovative Food Science & Emerging Technologies, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Modulation of the interfacial properties of TiN coatings to generate Rigid-Flexible SEI for better SiO anodes - Hebang Shi; He Zhang; Rui Wang; Ming Liu; Zihan Shen; Jingbo Chen; Binbin Wu; Maoqiao Xiang; Jun Li; Huigang Zhang; Pengpeng Lv; Qingshan Zhu (Chemical Engineering Journal, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Spatiotemporal difference of leachate production and its impact on the development and dynamics of LCS clogging - Ya Xu; Guangyuan Yao; Rui Xiang; Yuqiang Liu; Qifei Huang (Waste Management, 2023)

A stomatal optimization model adopting a conservative strategy in response to soil moisture stress - Rui Zhu; Tiesong Hu; Quan Zhang; Xiang Zeng; Shan Zhou; Fengyan Wu; Yong Liu; Yanxuan Wang (Journal of Hydrology, 2023)

Case-driven assessment of power grid emergency response capability considering typhoon disaster scenario diversity - Zhao-ge Liu; Xiang-yang Li; Dilawar Khan Durrani; Rui-jin Zhang (Journal of Cleaner Production, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Analytical solutions on non-Darcy seepage of grouted and lined subsea tunnels under dynamic water levels - Xiang Liu; Dongchi Wang; Yu Zhang; Annan Jiang; Qian Fang; Rui Zhang (Ocean Engineering, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Fluoroalkane modified cationic polymers for personalized mRNA cancer vaccines - Junyan Li; Yuanyuan Wu; Jian Xiang; Hairong Wang; Qi Zhuang; Ting Wei; Zhiqin Cao; Qingyang Gu; Zhuang Liu; Rui Peng (Chemical Engineering Journal, 2023)

Rapid, selective, and room temperature dissolution of crystalline xylan by a hydrotrope - Qiaoling Liu; Rui Tian; Ziwen Lv; Yuying Wu; Baozhong Lv; Xiang Hao; Zhimin Xue; Feng Peng (Carbohydrate Polymers, 2023)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

High-Frequency Repetitive Transcranial Magnetic Stimulation Regulates Astrocyte Activation by Modulating the Endocannabinoid System in Parkinson’s Disease - Xin Kang; Bing Zhang; Wanqing Du; Rui Zhao; Xuedong Liu; Ya Bai; Xiaobing Jiang; Jie Pang; Chenguang Zhao; Xiang Mou; Fang Gao; Hua Yuan; et al. (Molecular Neurobiology, 2022)

Validation of reliable safe harbor locus for efficient porcine transgenesis - Xiang Ma; Weijun Zeng; Lei Wang; Rui Cheng; Zeying Zhao; Caiyun Huang; Zhongxin Sun; Peipei Tao; Tao Wang; Jufang Zhang; Lu Liu; Xing Duan; et al. (Functional & Integrative Genomics, 2022)

Hierarchical collagen fibers complexed with tannic acid and Fe3+ as a heterogeneous catalyst for enhancing sulfate radical-based advanced oxidation process - Rui Wang; Ruiquan Yu; Junchao Wang; Jun Xiang; Chaojian Chen; Gongyan Liu; Xuepin Liao (Environmental Science and Pollution Research, 2022)

Roseococcus pinisoli sp. nov., lacking pufL and pufM bacteriochlorophyll a: synthesizing genes - Lei Shen; Miao-miao An; Rui-na Liang; Peng-xiao Liu; Xiang-wei He; Guo-zhu Zhao (Archives of Microbiology, 2022)

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Immune responses and protective efficacy of outer membrane protein ExbB of Pseudomonas fluorescens against Aeromonas hydrophila and Pseudomonas fluorescens affecting Carassius auratus - Wei Sun; Na Rong; Sijie Jian; Chao Kang; Chunlin Chen; Rui Chen; Rui Ding; Chen Chen; Xiang Liu (Aquaculture International, 2021)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

The TCP transcription factor PeTCP10 modulates salt tolerance in transgenic Arabidopsis - Yuzeng Xu; Huanlong Liu; Yameng Gao; Rui Xiong; Min Wu; Kaimei Zhang; Yan Xiang (Plant Cell Reports, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Study on NOx removal from simulated flue gas by an electrobiofilm reactor: EDTA-ferrous regeneration and biological kinetics mechanism - Nan Liu; Ying-ying Li; Du-juan Ouyang; Rui Guo; Run Chen; Wei Li; Ji-xiang Li; Ji-hong Zhao (Environmental Science and Pollution Research, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

Formation of nano- or near-nanoparticles via oxidation in the Dabaoshan concealed deposit, Guangdong Province - Rui Liu; Jianjin Cao; Yongkang Deng; Guoqiang Wang; Xiang Liu (Arabian Journal of Geosciences, 2020)

Mechanical characteristics of soil-rock mixtures containing macropore structure based on 3D modeling technology - Yong Liu; Shao-rui Sun; Ji-hong Wei; Jing-lei Song; Yong-xiang Yu; Wei He; Ji-xing Zhang (Journal of Mountain Science, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Salvianolic acid A attenuated myocardial infarction–induced apoptosis and inflammation by activating Trx - Rui Zhou; Jinhuan Gao; Changpei Xiang; Zhenming Liu; Yi Zhang; Jingjing Zhang; Hongjun Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Quality dependence of litter decomposition and its carbon, nitrogen and phosphorus release under simulated acid rain treatments - Hui Wei; Rui Ma; Jiaen Zhang; Leyi Zhou; Ziqiang Liu; Zhenyi Fan; Jiayue Yang; Xiaoran Shan; Huimin Xiang (Environmental Science and Pollution Research, 2020)

Natural HgS nanoparticles in sulfide minerals from the Hetai goldfield - Xiang Liu; Rui Liu; Genwen Chen; Xiaoen Luo; Meiqu Lu (Environmental Chemistry Letters, 2020)

Visualization and analysis of mapping knowledge domain of oxidation studies of sulfide ores - Rui Hong; Hui Liu; Chenglang Xiang; Yimeng Song; Chen Lv (Environmental Science and Pollution Research, 2020)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Reduced hemispheric asymmetry of brain anatomical networks in attention deficit hyperactivity disorder - Dandan Li; Ting Li; Yan Niu; Jie Xiang; Rui Cao; Bo Liu; Hui Zhang; Bin Wang (Brain Imaging and Behavior, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Three new phenylpropanoids from Lavandula angustifolia and their bioactivities - Shiyun Tang; Jianlian Shi; Chunbo Liu; Rui Jiang; Wei Zhao; Xin Liu; Nengjun Xiang; Yongkuan Chen; Qinpeng Shen; Mingming Miao; Zhihua Liu; Guangyu Yang (Natural Product Research, 2017)

Genomewide analysis of the lateral organ boundaries domain gene family in Vitis vinifera - HUI CAO; CAI-YUN LIU; CHUN-XIANG LIU; YUE-LING ZHAO; RUI-RUI XU (Journal of Genetics, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Serum CXCL12 Levels as a Novel Predictor of Future Stroke Recurrence in Patients with Acute Ischemic Stroke - Xiao-Lin Gu; Lin Liu; Xiang-Dong Lu; Zhen-Rui Liu (Molecular Neurobiology, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

A cycle slip fixing method with GPS + GLONASS observations in real-time kinematic PPP - Shirong Ye; Yanyan Liu; Weiwei Song; Yidong Lou; Wenting Yi; Rui Zhang; Peng Jiang; Yu Xiang (GPS Solutions, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Retinoic acid promotes primary fetal alveolar epithelial type II cell proliferation and differentiation to alveolar epithelial type I cells - Rui-wei Gao; Xiang-yong Kong; Xiao-xi Zhu; Guo-qing Zhu; Jin-shuai Ma; Xiu-xiang Liu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Ergosteroid derivatives from an algicolous strain of Aspergillus ustus - Xiang-Hong Liu; Feng-Ping Miao; Xiao-Rui Liang; Nai-Yun Ji (Natural Product Research, 2014)

Origin of the Miocene porphyries and their mafic microgranular enclaves from Dabu porphyry Cu–Mo deposit, southern Tibet: implications for magma mixing/mingling and mineralization - Song Wu; You-Ye Zheng; Xiang Sun; Sheng-Ao Liu; Rui-Rui Geng; Zhi-Ming You; Hai-Tao Ouyang; Dong Lei; Zhong-Ying Zhao (International Geology Review, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

Over-expression of integrin-linked kinase correlates with aberrant expression of Snail, E-cadherin and N-cadherin in oral squamous cell carcinoma: implications in tumor progression and metastasis - Dan Zhao; Xiu-Fa Tang; Kai Yang; Ji-Yuan Liu; Xiang-Rui Ma (Clinical & Experimental Metastasis, 2012)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Influence of soluble microbial products (SMP) on wastewater disinfection byproducts: trihalomethanes and haloacetic acid species from the chlorination of SMP - Yuan-yuan Wei; Yan Liu; Yun Zhang; Rui-hua Dai; Xiang Liu; Jin-jian Wu; Qiang Zhang (Environmental Science and Pollution Research, 2011)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

Complete genomic sequence analyses of Turnip mosaic virus basal-BR isolates from China - Hong-Yan Wang; Jin-Liang Liu; Rui Gao; Jia Chen; Yun-Hua Shao; Xiang-Dong Li (Virus Genes, 2009)

Identification and characterization of cyclin X which activates transcriptional activities of c-Myc - Xuanyang Li; Xiang Wang; Guoyuan Liu; Rui Li; Long Yu (Molecular Biology Reports, 2009)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)